An Inter-Generational Effect of Socio-Economic Status on Education Attainment in South Africa - Ratshivhanda, Thendo M.; Guvuriro, Sevias (Journal of Economics and Behavioral Studies, 2018)
Higher socio-economic status (SES) empowers an individual to have more access to a variety of materials relevant to achievements in life than would otherwise be possible. In theory, a child’s educational attainment can be influenced by hereditary and ecological variables; parents’ achievements are prompting children to achieve, or a deliberate investment that parents undertake in their children’s welfare, all suggestive of inter-generational effect in the process. A parent’s SES may therefore play a significant role in the child’s achievements. This paper attempts to determine the relationship between a parent’s SES and a child’s educational attainment and uses South African data collected at the national level. Employing descriptive statistics and OLS regressions, an inter-generational effect of parental SES positively influencing a child’s educational attainment is established. The finding supports policies promoting education as a fundamental poverty and inequality fighting mechanism in South Africa.